Adventure, rare and magical - Fenner, Phyllis Reid 1899- (A. A. Knopf, 1945)
A collection of fourteen thrilling or humorous fairy tales and stories from the world over, including "Seven at a Blow" and "The Bremen Town Musicians" by the Brothers Grimm, "Gears and Gasoline" by Caroline Emerson, and "The Tinderbox" by Hans Christian Andersen.